Lipid Changes During Endocrine Therapy in Breast Cancer Patients: The Results of a 5-Year Real-World Retrospective Analysis - He, Tao; Li, Xu; Li, Jiayuan; Wang, Zhu; Fan, Yuan; Li, Xiusong; Fu, Zhoukai; Wu, Yunhao; Lv, Qing; Luo, Ting; Zhong, Xiaorong; Chen, Jie (Frontiers in Oncology, 2022)
Background: The aim of this study was to investigate the status of serum lipids during endocrine therapy. Methods: We retrospectively analysed lipid profiles during the 5-year treatment of 1487 consecutive postoperative BC patients. Lipid parameters included triglycerides (TG), total cholesterol (TC), low-density lipoprotein (LDL-C) and high-density lipoprotein (HDL-C). Those biomarkers were measured at baseline and 1, 2, 3, 4 and 5 years following the initiation of endocrine therapy. Results: For premenopausal BC patients, LDL levels rapidly decreased at 1 year in the tamoxifen (TAM) group compared with baseline levels (p<0.05), and this decline remained for the following 4 years. Additionally, LDL levels were significantly lower in the TAM group than in the nonendocrine group at all assessment time points (p<0.05). Similarly, TC levels also decreased in the TAM group compared with baseline levels at all assessment time points (p<0.05), and compared with the levels in the nonendocrine group, TC levels were also lower for the first 4 years. For postmenopausal BC patients, there was no significant difference in the lipid profiles (TG, TC, LDL and HDL) in the letrozole (LET), anastrozole (ANA) or exemestane (EXE) groups compared with the nonendocrine group. For patients who received TAM, compared with the nonendocrine group, TC levels decreased at 1 year, and LDL levels decreased at 1 and 2 years. Conclusions: TAM may improve LDL and TC levels in premenopausal BC patients. In postmenopausal BC patients, aromatase inhibitors (AIs) may have no adverse effects on lipid profiles, and TAM may have limited beneficial effects on serum lipids.